Improving the Quality of Service of Fixed WiMAX Networks by Decreasing Application Response Time Using a Distributed Model - Lawal, Ibrahim A.; Ibrahim, Adamu A.; Zammarah , Nuha A. (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In the most recent few years, there has been a meteoric rise in the number of different wireless networks, as has the demand for wireless data services and multimedia applications. An improvement in quality of service (QoS) is required in order to meet the ever-increasing demand while also providing a service that is of a higher standard. One of the most cutting-edge technologies, known as World Wide Interoperability for Microwave Access (WIMAX), was developed with the quality of service in mind during its development. Despite utilizing the most recent advancements in technology, the WiMAX network continues to struggle with QoS performance issues. A brand new distributed Client-Server model was designed for the fixed WiMAX Network in order to reduce application response time. This was done in order to improve the quality of service performance. In order to make a comparison with the existing centralized model, the performance of the proposed model was analyzed with OPNET Modeler 16.0. According to the findings, the newly proposed distributed Client-Server system is capable of satisfying the requirements set forth by its users owing to an improvement in QoS performance in terms of application response time when compared to the conventional model. The performance of the network was increased by the deployment of more Base Stations (BSs), Subscriber Stations, and the utilization of client-server Base Stations that were chosen by the Nearest Neighborhood Algorithm that was devised